A facile direct spray-coating of Pebax® 1657: towards large-scale thin-film composite membranes for efficient CO₂/N₂ separation - Jiang, Xu (2022)
High-efficient CO2 capture using membrane separation technology is a promising approach towards environmental redemption in recent years. Thin-film composite (TFC) membrane with selective layer made of CO2-philic materials is the preferred membrane type for industrial-scale application, owing to its high permselectivity and good processability. Herein, we propose a facile direct spray-coating method to fabricate Pebax® 1657 thin-film on a porous polysulfone (PSF) substrate. Unlike most conventional multilayer TFC membranes, the unnecessary need for gutter layer in this work greatly simplifies the membrane fabrication process. Pebax® 1657 thin films were deposited through direct spraying of the polymer solution containing Pebax® 1657 on PSF substrate under ambient temperature. The as-prepared Pebax®1657 TFC membranes showed decent separation performances with CO2 permeance of >200 GPU and CO2/N2 selectivity of >50 for mixed gas (vol. (CO2)/vol. (N2) = 20/80) tests. The facile TFC membrane fabrication and good CO2 separation performances make the direct spray coated Pebax®1657 membranes a promising strategy for large-scale CO2 capture applications.